The influence of mini-fragment plates on the mechanical properties of long-bone plate fixation. Issue 3 (September 2019) - Knox, Riley; Curran, Patrick; Herfat, Safa; Kandemir, Utku; Marmor, Meir
Abstract: Objective: Mini-fragment plates (MFPs) are increasingly used in fracture surgery to provide provisional fixation. After definitive fixation, the surgeon decides whether to remove the plates or leave them in place as additional fixation, based on the perceived biomechanical influence of the MFP. However, there are no current biomechanical studies to guide this decision. Therefore, the purpose of this study was to evaluate the influence of MFPs on the four-point bending and torsional stiffness of long bone transverse and simple wedge fracture fixation constructs. Methods: Fourth-generation composite bone cylinders were cut to produce transverse (AO-OTA classification 12-A3) and simple wedge (AO-OTA classification 12-B2) fracture models. The specimens were fixed using a low-contact dynamic compression plate (LC-DCP) and MFPs. Specimens were tested in four-point bending and torsion utilizing 3 different MFP orientations. Results: No statistically significant differences in bending stiffness were found between control and MFP groups for transverse fracture constructs. MFPs significantly increased the bending stiffness for wedge fracture constructs under certain loading conditions. This increase was observed when MFPs were positioned both orthogonal (85.1% increase, P =  .034) and opposite (848.2% increase, P <  .001) to the LC-DCP. MFPs significantly increased the torsional stiffness for both transverse and wedge fracture constructs when MFPs were positioned both orthogonal (transverse: 27.7% increase, wedge: 16.7% increase) and opposite (transverse: 28.4%, wedge: 24.2% increase) to the LC-DCP. Conclusions: Our results indicate that including MFPs in definitive fixation can increase the bending and torsional stiffness of a long-bone fracture fixation construct. This suggests that the biomechanical influence of MFPs should be considered. However, clinical studies will be required to test the applicability of these findings to the clinical setting.